Leverage, Company Size, and Audit Quality Effect on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange and Malaysia Exchange for the 2015-2019 Period - St. Fadillah Hadaming; Apollo Daito (DINASTI RESEARCH, 2023)
State revenue from the manufacturing sector had the largest share during the period 2015 - 2019 in Indonesia and Malaysia but has not been able to increase the tax ratio due to indications of tax avoidance practices. This research looks at the elements that affect tax avoidance, including leverage, company size, and audit quality. Using certain criteria, 70 samples from the stock markets of both countries were selected, representing the population. Data research has revealed tax avoidance significantly affected by leverage, and size company, but not by the quality of audit. Meanwhile, tax avoidance is significantly influenced by leverage results, company size, and audit quality simultaneously. This study proposes a model for calculating the avoidance potential with the ETR accounting formula.